Role of oncology clinical pharmacist: a case of life-saving interventions - Al-Quteimat, Osama M.; Al-Badaineh, Mariam A. (International Journal of Basic & Clinical Pharmacology, 2017)
The oncology clinical pharmacist (CP) has a crucial role in cancer patient care through improving medication use including chemotherapy and other high alert medications. As part of multidisciplinary team CP has major role in assuring safe, effective and cost-effective drug therapy. Herein we report a case of 45 years old male patient diagnosed with diffuse large B-cell lymphoma (DLBCL), treated with high dose methotrexate (MTX) as prophylaxis for central nervous system (CNS) lymphoma, and followed up by CP regarding medications related issues. Role of CP is mainly to identify, prevent and manage any drug related problem including drug choice, dosage, interactions, administration and side effects. Oncology CP was very effective in optimizing medication use and has a promising role through providing clinically important interventions regarding medication use. We present this educational case report to show the vital role of CP in patient care by providing important interventions that are effective and sometimes life-saving.